IMSAR ANALISIS DETERMINAN PROFITABILITAS BANK BUMN SYARIAH DI INDONESIA - Imsar UINSU (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2022)
Islamic state-owned banks as one of the Islamic financial institutions must increase their profit continuously so that the performance of Islamic banking as measured by the return on assets ratio can continue to develop and advance. This study aims to analyze the bank's specific internal factors and macro-economic determinants that affect the profitability of Islamic state-owned banks. Using secondary data from 2011-2018, the results show that all independent variables used in this study, namely: variable capital adequacy (CAR), asset quality (NPF), liquidity (FDR) and operational efficiency (BOPO_ as an internal indicator, economic growth (EG) and inflation (INF) as an external indicator, affect the Profitability of Sharia BUMN Banks in Indonesia. The magnitude of the influence of the independent variables in profitability is R2 = 0.9998 percent, which means that the independent variables used affect the profitability of 99.98 percent.